AGN/Starburst Connection - Sani, Eleonora (České vysoké učení technické v Praze, 2014)
Two main physical processes characterize the activity in the nuclear region of active galaxies: an intense star formation (starburst, SB) and an Active Galactic Nucleus (AGN). While the existence of a starburst-AGN connection is undisputed, still it is not clear which process dominates the energetic output in both local and high redshift Universe. Moreover there is no consensus on whether AGN fueling is synchronous with star formation or follows it during a post-starburst phase. Here I first review how to disentangle the relative SB-AGN contribution, then I focus on the physical and geometrical properties of the circumnuclear environment.